Persepsi Guru dan Siswa Tentang IPS - Muhammad Kaulan Karima; Erni Erni; Radytha Nofitri Putri Agustin; Yasmina Awalunnisa; Lutfiah Nur Hanafi; Latu Malhayati; Meidina Firliani Rasika; Mutiara Nastiti; Zahra Rizki Ariesta (Politeknik Kampar, 2025)
This study was conducted to understand the perspectives of teachers and students regarding the Social Studies (IPS) subject at SD Negeri 1 Metro Pusat. The research employed a qualitative method, with data collected through interviews and documentation. The results indicated that teachers view Social Studies as an important subject that contributes to character building and students’ social understanding. On the other hand, students’ responses to the subject varied; some expressed a lack of interest due to monotonous teaching methods that were not connected to real-life contexts. The main issues identified were the lack of contextual approaches and the limited use of engaging learning media. Therefore, it is recommended that teachers apply methods that are more relevant to students' daily lives and utilize audiovisual media to enhance students' interest and understanding of Social Studies. A shared perception between teachers and students is essential for creating effective and enjoyable Social Studies learning